Strongman the extraordinary life of Hun Sen : from pagoda boy to Prime Minister of Cambodia - Mehta, Harish C. (Marshall Cavendish Editions, 2013)
Strongman: The Extraordinary Life of Hun Sen is the biography of the Cambodian leader whose private life has been a closely guarded secret. Fully updated and revised from the authors' first edition (Hun Sen: Strongman of Cambodia, published 1999), this volume is based on recently declassified archival documents and hours of new interviews with Hun Sen, his wife Bun Rany, son Hun Manet, other family members and associates. The book chronicles the life of Hun Sen from obscurity as a pagoda boy to strongman status. It reveals the life of Hun Sen and Bun Rany under the Khmer Rouge regime, their troubled romance as junior Khmer Rouge cadres, his escape to Vietnam, and triumphant return to liberate his country from genocide, and his emergence as the longest-serving leader in Southeast Asia.